Insight into the polymerization mechanism of photoinduced step transfer-addition & radical-termination (START) polymerizations. Issue 26 (22nd June 2017) - Xu, Tianchi; Zhang, Lifen; Cheng, Zhenping; Zhu, Xiulin
Abstract : The intrinsic polymerization mechanism of photoinduced step transfer-addition & radical-termination (START) has been revealed based on the successful construction of a catalytic system (Ru(bpy)3 Cl2 /RA) and a solvent system (DMC/MeCN). Abstract : Photoinduced step transfer-addition & radical-termination (START) polymerization is a newly developed polymerization strategy for the preparation of perfluorocarbon-containing alternating copolymers and was carried out under irradiation with blue light emitting diodes (LEDs) at room temperature (25 °C). In this work, the polymerization efficiency was further enhanced through optimization of the solvent system and construction of an efficient catalytic system: Ru(bpy)3 Cl2 /reducing agent (RA). In dimethyl carbonate (DMC)/acetonitrile (MeCN), the polyaddition between α, ω-diiodoperfluoroalkanesA and α, ω-unconjugated dienesB predominated over the chain transfer reaction, generating the target polymer product(AB) n with a relatively high molecular weight. Detailed analyses of a template reaction revealed the intrinsic polymerization mechanism of the START process. Based on a comprehensive investigation of the polymerization process, guidelines for the selection of appropriate RAs ( e.g., l (+)-ascorbic acid sodium salt (AsAc-Na) and Fe(0)) are provided herein.